Financial Factors Affecting Profitability in the Indonesian Food and Beverage Industry Post-Pandemic - Fitria Fatma; Siti Nurlaela; Yuli Chomsatu Samrotun (Owner : Riset dan Jurnal Akuntansi, 2026)
This research aims to analyze the influence of liquidity, capital structure, company size, and working capital efficiency on the profitability of food and beverage companies listed on the Indonesia Stock Exchange during the post-pandemic period 2021–2024. This research uses a quantitative approach with panel data regression methods. The selection of the estimation model was carried out through a series of model selection tests, and the Random Effect Model was used as the best model. The research results show that liquidity and capital structure have a significant negative effect on profitability, company size has a significant positive effect, while working capital efficiency has no significant effect. These findings indicate that in the post-pandemic recovery period, the company's financial strategy tends to be defensive, so that the increase in current assets and leverage is not fully able to encourage increased profits. On the other hand, business scale is a relatively consistent factor in increasing company profitability. This research provides an empirical contribution by showing that the relationship between financial indicators and profitability is contextual and influenced by the phase of the economic cycle. It is hoped that the results of this research can be a reference for company management, investors and future researchers in understanding the dynamics of profitability of the food and beverage industry in the post-crisis period.